English in the dalit context - Alladi Uma (ed.); Suneetha Rani K (ed.); Murali Manohar D (ed.) (Orient black swan, 2014)
Proceedings of the National Seminar on English in the Dalit Context organised by the UGC-DSA Programme, Department of English, University of Hyderabad in 2011.